2016
DOI: 10.1080/02755947.2015.1125976
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Diet of Juvenile White Sturgeon in the Upper Columbia River Canada with Lethal and Nonlethal Methods

Abstract: We describe the overall composition and prey selectivity in the diet of hatchery‐reared juvenile White Sturgeon Acipenser transmontanus in the upper Columbia River, Canada. The efficacy of two sampling methods, nonlethal gastric lavage and lethal sampling to remove stomach contents, were evaluated across different ages, size‐classes, and river sections. Gastric lavage samples were collected from 108 fish angled in October 2012 and 2013. In 2012 only, a subsample of 48 individuals were euthanized following gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Juveniles (<60 cm TL) feed on tube‐dwelling amphipods, mysids, isopods, Corophium , and other benthic invertebrates such as chironomids, and on the eggs and fry of other fish species (Schreiber, ; Radtke, ; Cochnauer, ; Partridge, ; PSMFC, ; Parsley et al., ). In the upper Columbia River, diet analysis of age‐1 to age‐10 juvenile WS indicated that Mysis relicta were the primary component of the diet followed by Trichoptera nymphs; other prey items encountered (in decreasing order of abundance) were Ephemoptera nymphs, snails, Diptera, fish parts, Gammaridae, Hemiptera, and Plecoptera (Crossman et al., ). As WS grow (~60–80 cm TL), their diets diversify and they begin to eat fish (Muir et al., ; PSMFC, ).…”
Section: Behaviourmentioning
confidence: 99%
“…Juveniles (<60 cm TL) feed on tube‐dwelling amphipods, mysids, isopods, Corophium , and other benthic invertebrates such as chironomids, and on the eggs and fry of other fish species (Schreiber, ; Radtke, ; Cochnauer, ; Partridge, ; PSMFC, ; Parsley et al., ). In the upper Columbia River, diet analysis of age‐1 to age‐10 juvenile WS indicated that Mysis relicta were the primary component of the diet followed by Trichoptera nymphs; other prey items encountered (in decreasing order of abundance) were Ephemoptera nymphs, snails, Diptera, fish parts, Gammaridae, Hemiptera, and Plecoptera (Crossman et al., ). As WS grow (~60–80 cm TL), their diets diversify and they begin to eat fish (Muir et al., ; PSMFC, ).…”
Section: Behaviourmentioning
confidence: 99%
“…High use of the HLK Eddy for feeding (e.g. benthic prey; Crossman et al 2016) and overwintering has been identified for white sturgeon (Fisheries and Oceans Canada 2014, BC Hydro 2016). The HLK Tailrace consists of discharge from HLK and is a deep pool (10 m) that shallows (< 5 m) where it joins the ALH Tailrace.…”
Section: Study Areamentioning
confidence: 99%
“…Sampling was conducted in both Canada and the United States, though the primary study site was located in Canada, throughout a 57-km reach of the LCR, between Hugh L. Keenleyside Dam (river kilometer [rkm] 0.0) and the United States-Canada border (rkm 57) in British Columbia, Canada (Figure 1). Sampling was divided among three zones, which were delineated by differences in discharge, available habitat, and previous data on differences in growth (BC Hydro, 2018) and diet (Crossman et al, 2016).…”
Section: S Tudy Are Amentioning
confidence: 99%